Rational Engineering of Phenylalanine Accumulation in Pseudomonas taiwanensis to Enable High-Yield Production of Trans-Cinnamate - Otto, Maike; Wynands, Benedikt; Lenzen, Christoph; Filbig, Melanie; Blank, Lars M.; Wierckx, Nick (Frontiers in Bioengineering and Biotechnology, 2019)
Microbial biocatalysis represents a promising alternative for the production of a variety of aromatic chemicals, where microorganisms are engineered to convert a renewable feedstock under mild production conditions into a valuable chemical building block. This study describes the rational engineering of the solvent-tolerant bacterium Pseudomonas taiwanensis VLB120 towards accumulation of L-phenylalanine and its conversion into the chemical building block t cinnamate. We recently reported rational engineering of Pseudomonas towards L-tyrosine accumulation by the insertion of genetic modifications that allow both enhanced flux and prevent aromatics degradation. Building on this knowledge, three genes encoding for enzymes involved in the degradation of L-phenylalanine were deleted to allow accumulation of 2.6 mM of L phenylalanine from 20 mM glucose. The amino acid was subsequently converted into the aromatic model compound t-cinnamate by the expression of a phenylalanine ammonia-lyase (PAL) from Arabidopsis thaliana. The engineered strains produced t cinnamate with yields of 23% and 39% Cmol Cmol-1 from glucose and glycerol, respectively. Yields were improved up to 48% Cmol Cmol-1 from glycerol when two enzymes involved in the shikimate pathway were additionally overexpressed, however with negative impact on strain performance and reproducibility. Production titers were increased in fed-batch fermentations, in which 33.5 mM t-cinnamate were produced solely from glycerol, in a mineral medium without additional complex supplements. The aspect of product toxicity was targeted by the utilization of a streamlined, genome-reduced strain, which improves upon the already high tolerance of P. taiwanensis VLB120 towards t-cinnamate.